KOMPOSISI DAN DISTRIBUSI TUMBUHAN BAWAH PADA AREAL DEMPLOT RESTORASI PASCA ERUPSI GUNUNG MERAPI TAHUN 2010 - , RACHMANTYO PUTRO P ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Merapi forest area is one of the mountainous forest area in Indonesia. This area has a variety of functions that can be viewed from various aspects and points of view, the most important is the ecological function. Merapi area is an area that is vulnerable to volcanic eruption, considering that this mountain is a part of the ring of fire on the island of Java, which is still active. Disasters occurred in late 2010 has led to changes in condition of the area, one of it is the changes of understorey condition related to succession. Understorey species has role as a ground cover to prevent the run-off. This study aims to determine the plant species composition and spatial distribution patterns of understorey on Restoration Demplot after the 2010 Mount Merapi Eruption. Methods of data collection in the field was conducted using systematic sampling with random start. The line were made by taking a perpendicular distance of 10 m from the road edge to the inner side (towards Kali Kuning) with space between line 250 m. Each line was divided into several 2 m x 2 m plots to observe the understorey with a spacing between plot of 5 m. Data collection had been done by identifying the undergrowth species and calculating the coverage percentage of each apecies. Data analysis was performed by calculating the Importance Value Index (IVI) on each spesies and determine the patterns of spatial distribution using the Dispersion Index and the signification test using Chi-squre. The results showed that there were 20 understorey species cosisting 11 families. There were 2 understorey spesies dominated this area. This species derived from Poaceae, which were Panicum muticum with IVI 32,80% and Eragrostis tenella with IVI 28,55%. There were 4 other spesies with IVI more than 10% and the remaining 14% spesies have IVI less than 10%. The 20 understorey spesies found in Restoration Demplot area has random distribution pattern.